Ressentis contre-transférentiels, relances en miroir et réflexivité inconsciente dans un entretien clinique à visée de recherche consacré à l'enseignement de la philosophie au lycée - Dominique Renauld (Éducation et Socialisation)
This article aims to examine the impact of mirror prompts on the conduct of a non-directive clinical interview for research purposes. If the latter can contribute to arouse certain effects of meaning on an interviewee by promoting in the latter the emergence of psychic resonances from the free associations aroused by the instruction, reflective prompts may themselves be subject to unconscious psychic processes leading a researcher to ask the interviewee on a particular point resonating, or mirroring, with his own story. In this case, when the latter mirror the interviewer’s psyche, but unbeknownst to the interviewer, can we speak of unconscious reflexivity? Thus, this article proposes some hypotheses about these prompts through the analysis of fragments of a clinical interview taken from a research in educational sciences devoted to philosophy teaching in high school.